Introduction: Volatility in finance, art, and culture - Benjamin Lee; Emily Rosamond (Finance and Society, 2023)
The term "volatility" applies to changeability: both that which can be measured, such as temperatures and stock prices, and that which cannot be easily measured, such as affects and emotions. Quantitative financial volatility has typically been studied quite separately from art, culture, and everyday life. Randy Martin's work, which addressed the resonances between volatility in dance and finance, was a notable exception. Martin focused on derivatives, which played a critical role in the development of financialized capitalism, especially between 1973-2008. Arguably, however, derivatives are no longer the key drivers of volatility as a social and cultural logic. New assemblages of asset managers, rentiers, and online platforms - along with a pandemic, new banking crises, and ongoing climate emergency - are reshaping how volatility is produced and navigated. How might we rethink volatility in order to better grasp its changing logics? This introduction unpacks existing debates on volatility in finance, art, and culture, suggesting several directions in which new work in this area might depart from existing frameworks - some of which are pursued in this special issue. We focus on three broad lines of exploration: rethinking the intellectual histories of volatility; rethinking volatility across disparate post-2008 contexts; and imagining volatile futures through art practice.
Keywords: 300; art; crisis; culture; derivatives; finance; futures; options; Volatility